2015
DOI: 10.1007/978-3-662-44605-8_2
|View full text |Cite
|
Sign up to set email alerts
|

Pruritus Epidemiology and Quality of Life

Abstract: The burden of chronic pruritus is increasingly recognized as significant worldwide. As wet-laboratory researchers investigate the pathophysiology of chronic pruritus, epidemiologists and health services researchers are quantifying the impact of pruritus by incidence, prevalence, and quality of life measures. Outcomes researchers are also investigating factors that may predict chronic pruritus incidence and severity. Such efforts will direct resources for research, public health intervention, and clinical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 134 publications
3
25
0
1
Order By: Relevance
“…In particular, respondents indicated that the most urgent topics in PN are the need for consensus regarding the classification and terminology of the condition, and new therapies. 17 For many patients with PN, the most important symptom to treat is often pruritus because of its impact on quality of life; 16,[18][19][20][21][22][23] however, pruritus is difficult to treat. Recently, the EADV published an expert consensus document on the definition, classification and terminology of chronic prurigo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, respondents indicated that the most urgent topics in PN are the need for consensus regarding the classification and terminology of the condition, and new therapies. 17 For many patients with PN, the most important symptom to treat is often pruritus because of its impact on quality of life; 16,[18][19][20][21][22][23] however, pruritus is difficult to treat. Recently, the EADV published an expert consensus document on the definition, classification and terminology of chronic prurigo.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep disturbance has been demonstrated to have serious consequences, including poor health, missed workdays and doctor visits owing to other skin conditions. 17 For many patients with PN, the most important symptom to treat is often pruritus because of its impact on quality of life; 16,[18][19][20][21][22][23] however, pruritus is difficult to treat. 4,8,9 Treatment for PN is commonly standardized, and the goal of therapy is often to manage pruritus.…”
Section: Discussionmentioning
confidence: 99%
“…[70] Epidemiological studies have emphasised the high global incidence and economic costs of itch. [71] The impact of chronic itch, duration >6 weeks, is comparable to that of chronic pain. [68] Itch occurs on diseased or non-diseased skin, and underlying diseases can be dermatological, systemic (eg chronic kidney disease, cholestasis), neurological or psychiatric, drug reactions or diseases of pregnancy.…”
Section: Itch Aetiology and Transmission To The Brainmentioning
confidence: 99%
“…Chronic itch severely impedes patients’ quality of life and affects an estimated 8–16% of the Western population. This places chronic itch among the most burdensome aspects of dermatological diseases . Therefore, effort is needed to find new potential targets to be exploited in the development of new therapies.…”
mentioning
confidence: 99%
“…This places chronic itch among the most burdensome aspects of dermatological diseases. [1][2][3][4] Therefore, effort is needed to find new potential targets to be exploited in the development of new therapies. The urge to scratch aims at removing the source of itch, like insects, plants or other forms of irritation, at the same time acting as a counterstimulus able to reduce the itch sensation.…”
mentioning
confidence: 99%